2012
DOI: 10.3892/mmr.2012.1086
|View full text |Cite
|
Sign up to set email alerts
|

C677T methylenetetrahydrofolate reductase gene polymorphism as a risk factor involved in venous thromboembolism: A population-based case-control study

Abstract: Abstract.The aim of the current study was to investigate the possible correlation between the C677T methylenetetrahydrofolate reductase (MTHFR) polymorphism and venous thromboembolism (VTE) in a population-based case-control study. Homocysteine (Hcy) was quantified by Abbott IMx immunoassay; screening for C677T MTHFR substitution was performed by polymerase chain reaction (PCR) and restriction analysis. The results from the two groups (440 patients and 440 controls) revealed that the frequency of T alleles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The frequency of MTHFR 677TT genotype was 28.38% in Uygur VT patients and 27.03% in Han VT patients, versus 12.79% and 14.92% in respective control individuals. Similar results were reported by Yin et al in a case-control study conducted in Shandong Province in China [38]. Also, Jang et al postulated that the presence of MTHFR 677TT genotype was associated with an increased risk of VT in Koreans [39].…”
Section: Prosupporting
confidence: 83%
“…The frequency of MTHFR 677TT genotype was 28.38% in Uygur VT patients and 27.03% in Han VT patients, versus 12.79% and 14.92% in respective control individuals. Similar results were reported by Yin et al in a case-control study conducted in Shandong Province in China [38]. Also, Jang et al postulated that the presence of MTHFR 677TT genotype was associated with an increased risk of VT in Koreans [39].…”
Section: Prosupporting
confidence: 83%
“…Yin et al . [ 12 ] reported that the frequency distribution of the TT genotype of MTHFR in the venous thrombosis group was higher than in the control group and the TT genotype of MTHFR C677T may be a genetic risk factor for DVT. Hyperhomocysteinemia is considered an independent risk factor for venous thrombotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…DNA analysis revealed the heterozygote form of methylenetetrahydrofolate reductase (MTHFR) mutation. This hereditary disorder is often connected to folic acid and vitamin B12 metabolism, and if patient has a normal level of homocysteine it is not clinically significant for the hemostatic disorder [12,13]. …”
Section: Discussionmentioning
confidence: 99%